A systematic literature review on comparative study of request for the past ten years (2012-2022) - Pang, Ming; Halim, Hazlina Abdul; Jalis, Farhana Muslim Mohd; Hu, Wei (Ritchmann Publishing Ltd, 2023)
This systematic literature review attempts to examine the current status, unsolved issues and future trend of the comparative study of request speech act for the past ten years (2012-2022). Based on the analysis of 186 studies, the findings are: 1) the status quo is that intralingual comparative studies of request are still very few and previous researches reply on DCT and CCSARP instruments too much; 2) unsolved issues include further investigation of intralingual comparative request, Asian languages, and the development of new or more advanced instrument; and 3) future trend is that more comparative studies of request need to be conducted on Asian languages, especially Mandarin and Malay from intralingual perspective and new or more advanced data collection and analysis instruments should be applied. This systematic literature review could help identify the research gap and unsolved problems in the current literature that calls for the further investigation of comparative request speech act.